2021
DOI: 10.1093/bioinformatics/btab344
|View full text |Cite|
|
Sign up to set email alerts
|

NeoFox: annotating neoantigen candidates with neoantigen features

Abstract: Summary The detection and prediction of true neoantigens is of great importance for the field of cancer immunotherapy. We searched the literature for proposed neoantigen features and integrated them into a toolbox called NeoFox (NEOantigen Feature toolbOX). NeoFox is an easy-to-use Python package that enables the annotation of neoantigen candidates with 16 neoantigen features. Availability NeoFox is freely available as an ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 9 publications
0
24
0
Order By: Relevance
“…Neoantigen candidates from SNVs and INDELs were identified with an in-house property pipeline 25 (“iCaM2”) and candidates from fusion genes were identified with EasyFuse 29 . Neoantigen candidates were annotated with features and subjected to prioritization algorithms using NeoFox 15 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Neoantigen candidates from SNVs and INDELs were identified with an in-house property pipeline 25 (“iCaM2”) and candidates from fusion genes were identified with EasyFuse 29 . Neoantigen candidates were annotated with features and subjected to prioritization algorithms using NeoFox 15 .…”
Section: Resultsmentioning
confidence: 99%
“…Our results indicated that integrating the quantitative approach relying on the neoantigen candidate load and the qualitative multiple instance approach may improve the prediction of the response to ICB. Furthermore, a limited set of neoantigen features was integrated into the model approach in this study, mostly targeting the linear sequence of neoantigen candidates and rather focusing on the interaction with MHC molecules 15 . Integrating clonality information 11 , structural features 45 and future features that specifically model the interaction between the MHC bound neoepitope candidate with the TCR repertoire may improve predictions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MHC binding is performed with the tool netMHCpan 4.1 [16] with the following parameters 'netMHCpan -p {fasta} -a {hla_allele} -s' for every epitope of 8, 9, 10 and 11 amino acids using NeoFox [20] API. We keep only the rank of the best binding for every allele independently.…”
Section: Methodsmentioning
confidence: 99%